2018
DOI: 10.1103/physreva.97.022313
|View full text |Cite
|
Sign up to set email alerts
|

Bang-bang shortcut to adiabaticity in trapped-ion quantum simulators

Abstract: We model the bang-bang optimization protocol as a shortcut to adiabaticity in the ground-state preparation of an ion-trap-based quantum simulator. Compared to a locally adiabatic evolution, the bang-bang protocol produces a somewhat lower ground-state probability, but its implementation is so much simpler than the locally adiabatic approach, that it remains an excellent choice to use for maximizing ground-state preparation in systems that cannot be solved with conventional computers. We describe how one can op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The procedure involves optimizing two parameters: the external parameter for the intermediate Hamiltonian and the holding time. In earlier work, the protocol was shown to work better for longer-range interactions [12].…”
Section: Introductionmentioning
confidence: 95%
“…The procedure involves optimizing two parameters: the external parameter for the intermediate Hamiltonian and the holding time. In earlier work, the protocol was shown to work better for longer-range interactions [12].…”
Section: Introductionmentioning
confidence: 95%
“…Finally, we should emphasize that the analytical and numerical methods proposed for smooth bang-bang control are useful in the field of quantum control, since the time-optimal bang-bang control are ubiquitous, for instance, in the atom cooling [49][50][51] and ground-state preparation [52,53]. Moreover, our results can be supplemented by machine learning [23,24,59] for the rapid transport with a harmonic trap [43][44][45] and optical lattice [60][61][62] in presence of noise or spinorbit coupling [63], and will be extended to other problems, including the load manipulation by cranes in classical system [64], and Brownian motion in statistical physics as well [65].…”
Section: Discussionmentioning
confidence: 99%
“…The smoother control input makes the experiments more feasible, and improve the overall performance of STA. Finally, we shall emphasize that our results can be easily extended to other different scenarios [49][50][51][52][53], although the smooth bang-bang control is applied here to atomic transport on a heuristic basis.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the numerically simulated result of such an experiment for the case of N=6 ions but otherwise similar parameters as discussed in Section 3.3.1. Since from these simulations we found that a fully adiabatic preparation of the ground state requires a too long time of hundreds of milliseconds, we use a non‐adiabatic bang‐bang scheme, similar to what has been used previously . With this procedure detailed in App.…”
Section: Examplesmentioning
confidence: 99%